Sweet Charlie, Dike, Cazzie, and Bobby Joe : high school basketball in Illinois - Bell, Taylor H. A., 1940- (University of Illinois Press, 2004)
"Far from the jaded professionals, the stories in Taylor Bell's Sweet Charlie, Dike, Cazzie, and Bobby Joe are of hungry young men playing their hearts out, where high-tops and high hopes inspire "hoop dreams" from Peoria to Pinckneyville, and Champaign to Chicago. Bell, a lifelong fan and authority on high school basketball in Illinois for more than 40 years, brings together for the first time the stories of the great players, teams, and coaches from the 1940s through the 1990s." "The book is titled for four players who reflect the unique quality of high school basketball, and whose first names are enough to trigger memories in fans who love the sport - Sweet Charlie Brown, Dike Eddleman, Cazzie Russell, and Bobby Joe Mason. Bell offers accounts of their exploits, told with a journalistic flair."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved.